“Enhancing Students’ Musical Competence through Interactive Multimedia in Music Education” - Ochilov Zayniddin Saypiddinovich (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2025)
ABSTRACT: This article investigates the role of interactive multimedia in developing students’ musical competence. It emphasizes how digital tools, including audio, video, and interactive platforms, can enhance learning outcomes by improving students’ practical skills, theoretical understanding, and creative abilities. The study highlights the pedagogical advantages of multimedia integration in fostering engagement, independent learning, and motivation in contemporary music education.